Optimizing Educational Management: The Principal's Approach to Providing Motivation and Treatment - Rini Handriani; Nanda Priatna; Badrudin (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the principal's leadership strategies in enhancing teacher synergy at SDN 103 Coblong. The research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation. The findings reveal that the principal prioritizes a humanistic approach, characterized by open communication, exemplary behavior, and interpersonal support, to foster a harmonious working environment. Challenges faced include miscommunication, internal conflicts, and low teacher awareness of their respective roles. The implemented strategies positively impact collaboration, mutual trust, and teacher motivation, resulting in strong synergy to achieve educational goals. This study contributes to the development of educational leadership theories and offers practical guidance for principals in building effective teamwork.